2007
DOI: 10.1634/theoncologist.12-2-156
|View full text |Cite
|
Sign up to set email alerts
|

Salvage Therapy in Hodgkin's Lymphoma

Abstract: Hodgkin's disease is a rare malignancy that affects approximately 7,500 patients per year in the U.S., leading to an estimated 1,400 deaths. The relapse rate for this disease varies from around 5% for early-stage disease to 35% for patients with advanced disease. Patients who relapse after chemotherapy have about a 20% cure rate with conventional salvage chemotherapy. Two randomized phase III studies have shown an improved failure-free survival rate with high-dose chemotherapy and autologous stem cell support … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
22
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 65 publications
0
22
0
1
Order By: Relevance
“…However, approximately 5% of early-stage disease and 30% to 40% of advanced stage disease relapse after first-line treatment. Patients with relapsed and refractory Hodgkin lymphoma typically receive salvage chemotherapy followed by ASCT (4). However, for patients who relapse after ASCT, effective therapeutic options are limited.…”
Section: Introductionmentioning
confidence: 99%
“…However, approximately 5% of early-stage disease and 30% to 40% of advanced stage disease relapse after first-line treatment. Patients with relapsed and refractory Hodgkin lymphoma typically receive salvage chemotherapy followed by ASCT (4). However, for patients who relapse after ASCT, effective therapeutic options are limited.…”
Section: Introductionmentioning
confidence: 99%
“…Relapse rates for HL following first-line chemotherapy vary from around 5% for early stage disease to 35% for advanced disease [3,4,12]. Conventional salvage regimens for refractory or relapsed HL after first-line combination chemotherapy have a modest cure rate of about 20% [13].…”
Section: Introductionmentioning
confidence: 99%
“…The British National Lymphoma Investigation and the GHSG conducted two randomized phase III trials, which concluded that ASCT improves PFS, but failed to show an improvement in overall survival compared with conventional salvage chemotherapy in relapsed patients [14,15]. Gemcitabine, vinblastine, or vinorelbine can be used with moderate efficacy for palliation in patients who relapse after ASCT [12,[16][17][18][19][20]. Therefore, despite the impressive overall results in HL, there is considerable room for improvement in both upfront treatment and salvage settings, particularly for patients with adverse IPS, especially those older than age 60, patients with primary refractory disease, and/or patients whose disease relapses following ASCT.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive experience with agents such as gemcitabine, vinorelbine, and vinblastine has been described and is briefly summarized in Table 2. [31][32][33][34][35][36][37][38] Such an approach might allow for prolongation of life with good quality with the possibility of prolonged remission.…”
mentioning
confidence: 99%